A study on Impact of selected Human Resource practices on retention of research employees in research institutes. (International Journal of Scientific Research and Management (IJSRM), 2017)
Retention of talented research employees is herculean task. Due to globalization every country wants to focus on development of science and technology which necessitates more numbers of researchers to join research organization and remain there so that continuous development is sustained. Research in various fields is well thought and ongoing process across the globe. The country’s development depends on the technological and research development. Every country wants to design and develop a research programme by involving expert people to contribute in the national or international development with their novel ideas and innovations. The goal of every Research Institute is to engage young students in the field of research and development. These institutes implement the monetary and non-monetary aspects to motivate and retain such talented employees. Research Institutes, in addition to the routine office facilities, provide certain welfare facilities to research employees i.e. housing, medical, book grant allowances, update allowance, Leave Travel Concessions, Study leave, flexible hours, laptops, etc. This helps research employees to concentrate on their research work. This is part of their retention programme. One of the important factors for career development and retention is Job Security. Everyone wants to settle in the working life. If Job Security is provided or assured, then employees try to devote more time on their work. The same is the case of research employees. If job security is provided, the research employees work hard, put extra efforts on their research activities. They do not have to find other institute for better and secured job position. However, if job security is not given, the research employees leave the research institutes. In addition, there are various other reasons for research employees leaving the research institutes. The topic selected for research paper is more focused to the Retention of Research Employees carrying out their research in the selected Research Institutes. The topic is trying to bring out the obvious reasons why research employees leave such organization and steps for retention of such researchers working in selected research institutes.